Problematizing munchausen by proxy - De Beer, Maresa (Department of Psychology, 2023)
The study critically examines the psychiatric phenomenon of Munchausen by Proxy/Factitious Disorder by froxy. It provides a comprehensive examination of the literature, indicating the disagreement$ and lacunae. A critique of the literature is offered, with particular focus on the lack of attention to the historical and social predeterminations of Munchausen by Proxy, its diagnostic construction, its validity as a syndrome, the inadequacy of the clinical data, the recursively of the literature and its concomitant lack of attention to contextual factors contributing to the emergence of the phenomenon. A case history is used to illustrate the dominant practices and discourses as well as the difficulties encountered in the clinical work. The study concludes with some questions raised by such cases and offers a few suggestions regarding the contribution of the clinical psychologist in addressing these questions.